Occupational exposure to hexavalent chromium, nickel and PAHs - Tavares, Ana Maria (2022)
Funding: This research was funded by European Unions’ Horizon 2020 research and innovation Programme under grant agreement No 733032 HBM4EU and co-funded by UIDP/00009/2020; UIDB/00009/2020 (Centre for Toxicogenomics and Human Health—ToxOmics, FCT).